MENUMBUHKAN KREATIFITAS DALAM MENDORONG PENINGKATAN TARAF KEHIDUPAN SOSIAL EKONOMI MELALUI KEGIATAN PENGABDIAN MASYARAKAT DI DESA CEMPLANG - Zidny, Robby (Universitas Sultan Ageng Tirtayasa, 2022)
Community service activities are the application of the Tri Dharma of Higher Education through across-scientific approach to solve problems at certain times and areas. This community service activitycarriesthetheme